The Use of Science Laboratories with Cookbook and Inquiry-Based Methods to Enhance Students' 21st-Century Thinking Skills - Putri, Meissy Nuraini; Malik, Adam (KULIDAWA, 2024)
The present study aims to: 1) interpret the role of laboratories in science learning and 21st-century academic skills; 2) evaluate the effectiveness of laboratories use with cookbook and inquiry-based science learning in improving students' 21st-century thinking skills. The study was conducted using a narrative literature review method, which involves independently collecting, reviewing, and synthesizing various previous studies in the library and journal house of UIN Sunan Gunung Djati Bandung and other reputable sources. The data sources are references (e.g. books and journal articles) from reputable publishers. The results indicate that: 1) the laboratory use with the cookbook method provides structured and easy-to-follow experimental procedures, while with the inquiry method, it encourages students' independent exploration and problem solving; 2) the combination of these two methods can strengthen conceptual understanding and basic laboratory techniques, as well as develop students' critical thinking skills, creativity, collaboration, and digital literacy. The implications of the present study are the need to integrate the cookbook and inquiry methods in the science curriculum to prepare students to face the challenges of the 21st century.